2016
DOI: 10.4244/eijv12i7a139
|View full text |Cite
|
Sign up to set email alerts
|

A computational atlas of normal coronary artery anatomy

Abstract: A computational atlas of normal coronary artery anatomy provides distributions of diameter, lengths and bifurcation angles as well as more complex shape analysis. These data define normal anatomical variation, facilitating stent design, selection and optimal treatment strategy. These population models are necessary for accurate computational flow dynamics, can be 3D printed for bench testing bifurcation stents and deployment strategies, and can aid in the discussion of different approaches to the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Mean "reference" diameter, derived from a large intravascular ultrasound (IVUS) study 3 , is 5 mm, and ranges between 3.5 and 6.5 mm. After a mean length of 10.5±5.3 mm 4 , the LM divides into the left anterior descending artery (LAD) and the left circumflex artery (LCX). In up to 25% of cases, a distal trifurcation exists due to the presence of an intermediate branch.…”
Section: Left Main Stem Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…Mean "reference" diameter, derived from a large intravascular ultrasound (IVUS) study 3 , is 5 mm, and ranges between 3.5 and 6.5 mm. After a mean length of 10.5±5.3 mm 4 , the LM divides into the left anterior descending artery (LAD) and the left circumflex artery (LCX). In up to 25% of cases, a distal trifurcation exists due to the presence of an intermediate branch.…”
Section: Left Main Stem Anatomymentioning
confidence: 99%
“…In up to 25% of cases, a distal trifurcation exists due to the presence of an intermediate branch. Importantly, the size of the normal LM and its bifurcation into the LAD and LCX is predictable using fractal geometry and Finet's law 4 . Although being variably oriented in the three dimensions, LM bifurcation geometry is often summarised according to the distal bifurcation angle (also called angle B) which is highly variable but often wide (higher than other coronary bifurcations), with a mean estimated value of 70-80° 4 .…”
Section: Left Main Stem Anatomymentioning
confidence: 99%
“…Traditional clinical approaches to the quantification of vascular bifurcation shape focus almost entirely on simple geometric parameters such as diameter and angle, with their averages determined independently within various populations [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ]). Previously, we published selected basic measures such as angles and diameters [ 7 ], and we investigated the use of centrelines and cross-sectional shape data to create an average coronary artery model using tree-spaces [ 8 ]. In this work, we present a robust methodology to register any computer-aided design (CAD) to a correspondenceless population of shapes, and apply it to build a large expert-reviewed fully 3D atlas of vessel bifurcations.…”
Section: Introductionmentioning
confidence: 99%
“…Let us consider a vessel with a diameter d 0 , which splits into two branches with diameters d 1 and d 2 (Fig. 1), then according to Murray's law Experimental studies have shown that Murray's law is also true for tubules of some leaves [2], but more accurate measurements showed deviations from Murray's law in the vascular system [3][4][5][6][7]. These tests were performed using CT (computed tomography), IVUS (intravascular ultrasound), direct post mortem measurements, etc.…”
Section: Introductionmentioning
confidence: 99%